FACTORS INFLUENCING INTENTION TO USE ELECTRONIC BANKING IN EAST ALGERIA - Ahcène TIAR; Aissa ROUABHIA; Ilyes BOUDJAADA; Tahar DJELLIT (Business Excellence and Management)
This study aims to examine the factors influencing customers’ intention to use electronic banking (e-banking) in East Algeria. The proposed conceptual model is based on the Technology Acceptance Model (TAM) with its original postulates: perceived usefulness and perceived ease of use, which is extended to embrace some factors, including perceived risk, awareness, self-efficacy, social influence and resistance to change. The empirical data are collected from a questionnaire survey of 170 valid responses and analysed using the Partial Least-Squares Structural Equation Model (PLS-SEM) approach and Smart-PLS 4. The results show that bihavioural intention to use e-banking is influenced directly by perceived usefulness and ease of use and indirectly impacted by self-efficacy.